EFFECTS OF DIFFERENT ADJUVANTS UPON IMMUNOGENICITY OF ANTI-GROUP B STREPTOCOCCAL VACCINE COMPONENTS - A. N. Suvorov; G. F. Leontyeva; L. F. Meringova; K. B. Grabovskaya; T. V. Gupalova; E. I. Vorobyeva; A. S. Simbirtsev; A. A. Kolobov; Artem A. Totolian (Медицинская иммунология)
Abstract. Design of an effective and safe vaccine against pathogenic streptococci is still on the agenda, in spite of numerous attempts in this area undertaken by different laboratories. In order to improve immunogenicity of recombinant vaccine preparations, a selection of effective adjuvants is necessary. Previously, two recombinant GBS polypeptides P6 and ScaAB were found to be immunogenic, and their injection in separate preparations or mixed manner boosted production of specific and protective antibodies with high affinity. Four different adjuvants (Freund adjuvant, aluminum hydroxide, Bestim and Interleukine-1β) have been tested for immunization of mice with single polypeptides, or with their mixtures. As a result of vaccination, it was demonstrated that aluminum hydroxide was providing the most desirable immunological parameters of immune response among the adjuvants tested. A mixture of polypeptides containing aluminum hydroxide was found to produce specific antibodies with better opsonizing activity against group B streptococci. (Med. Immunol., 2008, vol. 10, N 2-3, pp 215-222).